The Effect of Problem-Based Learning Model on the Ability to Recognize Geometric Shapes in Children Aged 5-6 Years - Saining, Munirah; Rusmayadi, Rusmayadi; Musi, Muhammad Akil; Halik, Abdul (PT. Riset Press International, 2025)
This study aims to find out the overview of the problem-based learning (PBL) learning model on the ability to recognize geometric shapes of children aged 5-6 years and to determine the influence of the Problem Based Learning (PBL) model on the ability to recognize geometric shapes of children aged 5-6 years. The approach used is a quantitative approach with a type of Quasi Experimental research with a research design, namely a nonequaivalent control group design. The population in this study is children aged 5-6 years. The sampling in this study is cluster random sampling. The sample in this study is 14 children with 7 children as the experimental group and 7 children as the control group. The data analysis techniques used are descriptive statistical analysis and non-parametric statistical analysis. The results of data analysis obtained Asym (2-tailed) = 0.017 < 0.05 HI accepted and H0 rejected, meaning that the geometry ability of children who were treated with the problem-based learning model in the experimental group experienced significant development compared to the control group. This shows that the problem-based learning learning model significantly influences the geometry ability of children aged 5-6 years.